(untitled) (Multidisciplinary Journal of Science and Technology, 2025)
This article analyzes the similarities and differences between flower names in English and Uzbek languages. It explores their linguistic structures, semantic meanings, and cultural symbolism. This study uses a descriptive-comparative method to analyze selected floral terms. The results show that in English, flower names are often simple nouns (e.g., rose, lily, tulip) or compound forms (sunflower, snowdrop, buttercup) and are heavily influenced by Latin and Greek origins. In contrast, in Uzbek, most flower names are either native Turkic or borrowed from Persian and Arabic, demonstrating the agglutinative nature of the Uzbek language through the common use of the suffix “-gul”. The discussion concludes that both languages use flowers as metaphors for human emotions, love, and beauty, yet each culture expresses these through its unique historical and poetic worldview.